Risiko psikososial pada tenaga kesehatan di rumah sakit: A literature review - Rahmila, Septa; Denny, Hanifa Maher; Dewi, Endah Kumala (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Medical personnel who are at the forefront of treating patients generally work optimally and without stopping. The unlimited number of overtime hours and the condition of health workers having to be on standby when needed as well as the erratic workload result in psychosocial risks for health workers. Purpose: To determine the psychosocial risks that occur among health workers in hospital. Method: Systematic literature review research uses the Population, Intervention, Comparison, Outcomes, Context (PICOC) approach. Literature search with the keywords